Crises in oil, gas and petrochemical industries. Volume 2, - Rahimpour, Mohammad Reza, 1961- (Elsevier, 2023)
Crises in Oil, Gas and Petrochemical Industries: Loss Prevention and Disaster Management, Volume Two provides an overview of both natural and manmade disasters occurring in oil, gas and petrochemical industries and prepares special solutions based on their types. The book focuses on loss prevention and disaster management in petrochemical industries from different points-of-view. Sections review methods for making the apparatus safer and continue with discussions on the process of facing and managing disasters during the occurrence. Final sections cover loss and economic analysis after disasters and methods of reversibility are presented with case studies from around the world.
Keywords: Petroleum industry and trade.; elektronické knihy; electronic books